Molecular Detection of Some Virulence Genes in Stahpylococcusaureus Isolated from Different Human Clinical Specimens (Medico Legal Update, 2020)
Staphylococcus aureus is a significantbacteria in numerous simple and more severe diseases of humansbecause it possessesmanyvirulence factors which controlled byvarious genes that promoteinvention of thehost cells.A total of Ninetyisolates of Staphylococcus aureus obtained from various human clinical specimensdistributed asurine samples (30/90) (33.3%), wound swabs (28/90) (31.1%), blood samples (24/90) (26.7%)and sputum swabs (8/90) (8.9%). The clinical specimens were submitted to diagnostic microbiologylaboratories of Al-Hillah Teaching Hospital,Babylon maternity and children’s Hospital and AL-MahaweelGeneral Hospital during the interval from April to September 2019, in Babylon Governorate, Iraq.The multiplex PCR assay was achieved to identify Fourselected virulence genes such as (sea, seb, eta andtst) in S. aureus strains by using specific primers and depending from sizes of the products PCR amplicons.Each90 isolates of S.aureus in human clinicalspecimens were examined.T he results revealed that,the mostfrequent gene is sea 74 (82.2%), followed by seb gene 71(78.9%), tstgene 44 (48.9%) and etagene 32(35.6%) was reported as the least frequent detected gene.Furthermore, it was found that, the predominancetoxin genes represent the highestrate in S.aureus strainsisolated from wound swabs 85 (38.5%), followed by bloodsamples 69(31.2%), urine samples 54(24.4%) andfinally the sputum swabs 13 (5.9%).